Bacteriome-Localized Intracellular Symbionts in Pollen-Feeding Beetles of the Genus Dasytes (Coleoptera, Dasytidae) - Weiss, Benjamin; Kaltenpoth, Martin (Frontiers in Microbiology, 2016)
Several insect taxa are associated with intracellular symbionts that provision limiting nutrients to their hosts. Such tightly integrated symbioses are especially common in insects feeding on nutritionally challenging diets like phloem sap or vertebrate blood, but also occur in seed-eating and omnivorous taxa. Here, we characterize an intracellular symbiosis in pollen-feeding beetles of the genus Dasytes (Coleoptera, Dasytidae). High-throughput tag-encoded 16S amplicon pyrosequencing of adult D. plumbeus and D. virens revealed a single gamma-proteobacterial symbiont (‘Candidatus Dasytiphilus stammeri’) that amounts to 52.4–98.7% of the adult beetles’ entire microbial community. Almost complete 16S rRNA sequences phylogenetically placed the symbiont into a clade comprising Buchnera and other insect endosymbionts, but sequence similarities to these closest relatives were surprisingly low (83.4–87.4%). Using histological examination, three-dimensional reconstructions, and fluorescence in situ hybridization, we localized the symbionts in three mulberry-shaped bacteriomes that are associated with the mid- to hind-gut transition in adult male and female beetles. Given the specialized pollen-feeding habits of the adults that contrasts with the larvae’s carnivorous lifestyle, the symbionts may provision limiting essential amino acids or vitamins as in other intracellular symbioses, or they might produce digestive enzymes that break up the fastidious pollen walls and thereby contribute to the host’s nutrition. In either case, the presence of gamma-proteobacterial symbionts in pollen-feeding beetles indicates that intracellular mutualists are more widely distributed across insects with diverse feeding habits than previously recognized.